PEMBUATAN DAN KARAKTERISASI KOMPOSIT KARBON ZnO NANOSTRUKTUR MENGGUNAKAN METODE DIP-COATING - Wetya Fatma Kumala Sari; Erman Taer; Rika Taslim (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The performance of activated carbon monoliths from rubber wood has been enhanced by modifying the surface through the addition of Zinc Oxide (ZnO) bydip coating method with immersion 30 minutes. The sample activated by combination of physical-chemical activation were named as E F and Carbon sample that had been grown nanoparticle ZnO were name as EK F. The physical properties, density crystalline, surface morphology and content element of the sample have been tested and analyzed. Density of E F was obtained 0,379 g.cm-3 and density value for sample EK F was obtained 0,390 g.cm-3. The measurement of Scanning Electron Microscope (SEM) showed the nanoparticle ZnO, and measurement of Energy Dispersive X-Ray (EDX) determines the atomic percentage of the element zinc, i.e 5,80%. Measurement of X-Ray Diffraction(XRD) showed the peaks of composite carbon electrode occurred at 2θ of 22,880 and 44,480 due to presence of carbon structure with their crystal orientation of (002) and (001). Electrochemical properties for carbon electrode cell and composite electrode carbon with the addition zinc oxide (ZnO) were analyzed using cyclic voltammetry. For carbon electrode without nanoparticle ZnO has specific capacitance of 53,90 F.g-1 and the specific capacitance for composite carbon electrode with immersing 30 minutes is 63,53 F.g-1. The result of the overall study showed that the modification carbon electrode with addition ofnanoparticle ZnO increased the values of specific capacitance electrode carbon for supercapacitor applications.